INTERFACE PROPERTIES AND CAPACITANCE-VOLTAGE BEHAVIOR OF INDIUM-PHOSPHIDE METAL-INSULATOR-SEMICONDUCTOR PREPARED BY PLASMA-ASSISTED OXIDATION - LIM, H; BAGLIO, JA; DECOLA, N; PARK, HL; LEE, JI; KANG, KN (AMER INST PHYSICS, 1991)
A remote plasma-enhanced oxidation method, with two different reactant gases of N2O and POCl3, is used to grow stable insulating layers on an InP substrate. The compositional profile of the oxide grown with N2O reactant was very similar to that of thermally grown oxide. The hysteresis of capacitance-voltage (C-V) characteristics in this system was relatively small and determined by the compensative effects of mobile charges in the oxide and the capture of electrons at the interface. The very unstable nature of the C-V characteristics in the metal-insulator-semiconductor (MIS) diode prepared with POCl3 reactant seems to be related to the gradual nature of the interface and/or the P-oxide deficiency at the interface. Even if a stable oxide layer of InPO4 can be grown by POCl3 plasma, the very poor nature of the transition region must be overcome to achieve a good MIS structure.
Keywords: INP; OXIDES; BAND